Transition-Metal-Free One-Pot Synthesis of Fused Benzofuranamines and Benzo[b]thiophenamines - Liu, Ran; Lv, Lili; Yang, Bingchuan; Gu, Ziyi; Li, Chenglong; Lv, Xueyan; Ding, Chengcheng; Huang, Xianqiang; Yuan, Dong (Molecules (Basel, Switzerland), 2023)
A series of benzofuran and benzo[b]thiophen derivatives was synthesized via a transition-metal-free one-pot process at room temperature. This one-pot protocol enables the synthesis of compounds with high reaction efficiency, mild conditions, simple methods, and a wide-ranging substrate scope. Regioselective five-membered heterocycles were constructed in good-to-excellent yields.